Produção científica na área da surdez: Análise dos artigos publicados na revista brasileira de educação especial no período de 1992 a 2013 - de Azevedo, Claudinéia Barboza [UNESP]; Giroto, Claudia Regina Mosca; Santana, Ana Paula de Oliveira (FapUNIFESP (SciELO), 2015)
This study aimed to map scientific literature on deafness published in the Brazilian Journal of Special Education since its creation in 1992 until 2013, so as to accompany the trajectory of how deafness and its specificities have been portrayed in productions aired this journal. Data collection allowed the identification of 49 articles. We considered for data analysis: annual distribution of this scientific production; type of authorship; author’s area of expertise; textual genre; types of research conducted; issues related to deafness; and therapeutic/educational approaches used. The results showed a trend of growth in this production in the periods related to changes in legislation. Double authorship, Education, Speech Therapy and Psychology prevailed as major areas of formation of authors. The most frequent type of publication were: research report, types of assessment, intervention and description; followed by essays and literature reviews. The theme Literacy was the most often related to deafness, and Bilingualism figured as the most emphasized approach. It is worth emphasizing the importance of this journal for disclosure, visibility and accessibility of published articles on deafness, due to the frequency of such publication and the diversity of issues related to this area, as well as the need to expand research that addresses the process of appropriation of L1 and L2, not only with regard to its instrumentalization, but also on the nature of teaching practices and contexts of use, in line with the language profiles of deaf enrolled in general education.
Scientific production in the area of deafness: Analysis of articles published in brazilian journal of special education from 1992 to 2013
Keywords: Brazilian journal of special education; Deafness; Special education